2015
DOI: 10.1186/s12885-015-1718-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cellular sphingosine-1-phosphate by sphingosine kinase 1 and sphingosine-1-phopshate lyase determines chemotherapy resistance in gastroesophageal cancer

Abstract: BackgroundResistance to chemotherapy is common in gastroesophageal cancer. Mechanisms of resistance are incompletely characterised and there are no predictive biomarkers in clinical practice for cytotoxic drugs. We used new cell line models to characterise novel chemotherapy resistance mechanisms and validated them in tumour specimens to identify new targets and biomarkers for gastroesophageal cancer.MethodsCell lines were selected for resistance to oxaliplatin, cisplatin and docetaxel and gene expression exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 50 publications
1
33
0
Order By: Relevance
“…Among three, the absolute level of SPHK1 expression was higher than two other mRNAs. In addition, the up‐regulation expression of SPHK1 in human GC has been reported previously , while the mechanism has not yet been fully clarified. Therefore, we chose SPHK1 as the object for follow‐up study.…”
Section: Resultsmentioning
confidence: 93%
“…Among three, the absolute level of SPHK1 expression was higher than two other mRNAs. In addition, the up‐regulation expression of SPHK1 in human GC has been reported previously , while the mechanism has not yet been fully clarified. Therefore, we chose SPHK1 as the object for follow‐up study.…”
Section: Resultsmentioning
confidence: 93%
“…6C). Sphingolipids have been attributed to, among others, insulin resistance, inflammation, and carcinogenesis (71)(72)(73). Detection of high levels of sphingolipids in the serum of obese animals could indicate the potential for susceptibility to many diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has shown that SGPL1 gene is associated with drug resistance in GC cells. 25 In this study, we found that miR-449a is the potential upstream regulator of SGPL1. Overexpression of miR-449a reduced the activity of luciferase reporter gene containing SGPL1 3 0 UTR region, while the variation of seed area in SGPL1 3 0 UTR could reverse the regulation role of miR-449a.…”
Section: Discussionmentioning
confidence: 82%